Analisis Faktor-Faktor yang Mempengaruhi Pendapatan Pedagang Sayur di Pasar Pabaeng-Baeng Kota Makassar - Andi Indra; Tahir, Thamrin; Dinar, Muhammad; Hasan, Muhammad; Nurdiana (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2023)
The main objective of this research is to partially assess the influence of capital variables, working hours, length of business, and business location on the income of vegetable traders operating at the Pabaeng-baeng market located in Makassar City. This research adopts a quantitative descriptive research design. The data obtained from the questionnaire came from a total of 44 respondents. Data analysis includes the use of descriptive statistical analysis and inferential statistical analysis. The results of this research show that the income of vegetable traders in the Pabaeng-baeng market in Makassar City is partially influenced by characteristics such as capital, length of business, and business location, while working hours partially have a negative influence on business income. Simultaneously, a vegetable trader's income is influenced by capital, working hours, length of business, and business location.